Analisis Bibliometrik Dari Sewindu Penelitian Tentang Asset Pricing - Ramadhani, Indi; Yanti, Pitri; Sari, Maya (JURNAL AKUNTANSI, 2023)
ABSTRACTThis study aims to present the development of asset pricing models from bibliometric analysis and provide scope and direction for future research. The Scopus database was used to search for research articles on asset pricing from 2016-2023. Out of 8,839 articles, 2,860 were selected for the final bibliometric analysis. Citation analysis, keyword analysis, and author-related analysis were conducted. Based on the results of bibliometric analysis, it is known that the United States is the country that conducts the most research on asset pricing. Keyword analysis was also analyzed to evaluate important areas of research. Financial markets, stock markets, costs, investment, price dynamics, risk assessment, commerce, CAPM, stock returns, asset pricing models, return predictability, risk factors, and profitability are the most frequently used keywords. The year 2021 had the highest number of research articles. The most prominent author in asset pricing research is Zaremba who has the highest citations.